Full force and effect ebook - Greaney, Mark (Jack Ryan, 2014)
President Jack Ryan faces a global threat on the verge of going nuclear in this thriller in Tom Clancy's #1 New York Times bestselling series. A North Korean ICBM crashes into the Sea of Japan. A veteran CIA officer is murdered in Ho Chi Minh City. A package of forged documents goes missing. The pieces are there, but assembling the puzzle will cost Jack Ryan, Jr., and his fellow Campus agents precious time. Time they don’t have...    The challenge facing President Jack Ryan is an old one with a terrifying new twist. As the international stalemate with North Korea continues into its seventh decade, a young, untested dictator is determined to prove his strength by breaking the deadlock. Like his father before him, he hangs his plans on the country’s nuclear ambitions, a program impeded by a lack of resources—until now. A recently discovered deposit of valuable minerals has caused a dramatic change in the nation’s economic fortune. Coupled with their nuclear capabilities, the money from this find will make North Korea a dangerous force on the world stage. There’s just one more step needed to complete this perfect plan...the elimination of the president of the United States.